TINJAUAN PERLAKUAN KHUSUS TERHADAP DEBITUR BANK PADA MASA PANDEMI COVID-19 DI BANK BCA KANTOR CABANG UTAMA SAMARINDA - Arifin, Billy (Universitas 17 Agustus 1945 Samarinda, 2022)
ABSTRACTIONThe emergence of Covid-19 greatly affected the growth of the economic and financial sectors in Indonesia. The government through the Financial Services Authority (OJK) has released a regulation on national economic stimulus due to the spread of Coronavirus Disease 2019 (Covid-19). As a form of support for this policy, BCA established a policy regarding credit restructuring as a form of special treatment given to Debtors affected by the 2019 Coronavirus Disease pandemic. The issue raised in this paper is how BCA Bank Samarinda Main Branch Office responds to the Financial Services Authority (OJK) Regulation. 2020 regarding the national economic stimulus as a countercyclical policy on the impact of the spread of coronavirus disease 2019 and whether special treatment of Debtors during the Covid-19 period affected the balance of interests between BCA Bank, Samarinda Main Branch Office and its debtorsThis type of research is a type of empirical legal research that is oriented to primary data (results of field research).The results showed that PT Bank Central Asia Tbk. (BCA) at both the Samarindan City branch office and all BCA branches in Indonesia fully supports government policies in an effort to prevent and cope with the Coronavirus Disease 2019 (Covid-19) pandemic. As a form of support, BCA establishes a policy regarding credit restructuring, namely providing relief to Debtor customers affected by Coronavirus Disease 2019 (Covid-19) in adjusting payment of obligations. BCA in this case provides relief or restructuring in several forms tailored to the condition of the debtor and / or the debtor's business. Through this stimulus policy, BCA views this step as a policy in accordance with objective conditions as an effort to protect the interests of the common economy. Through this stimulus policy, banks will also have the opportunity to have wider movement so that the formation of bad loans can be controlled and make it easier to provide new credit to their borrowers. By encouraging the optimization of banking performance, particularly the intermediation function, maintaining financial system stability and supporting economic growth. Keywords: Special Treatment Forests, Covid-19, BCA.